Pengaruh Faktor Sosial Ekonomi terhadap Pendapatan Usahatani Kopi Arabika di Desa Kendenan Kecamatan Baraka Kabupaten Enrekang - Nalaratih Uswa Lutfiah; Sri Mardiyati; Muh Ikmal Saleh (Paspalum: Jurnal Ilmiah Pertanian, 2023)
The aim of this study was to determine the production and income of Arabica coffee farming, to analyze the factors that influence the production of Arabica coffee farming, to determine the effect of socio-economic factors on Arabica coffee farming income in Kendenan Village, Baraka District, Enrekang Regency. The population in this study were 120 people and 25% were taken. The sample was determined using simple random sampling technique. The samples obtained were 30 people. The data analysis used is income analysis and multiple linear regression. The results showed that the production of arabica coffee farming was 498.5 kg per hectare and the income of arabica coffee farming was IDR 9,122,887.50 per hectare. Factors that influence the production of Arabica coffee farming simultaneously are the area of land, the amount of fertilizer, labor, farming experience and the length of time they have attended formal education. Factors that significantly influence the production of Arabica coffee farming are land area and number of workers. Socio-economic factors that significantly influence the income of Arabica coffee farming are land area, labor wages and farming experience. 1. if the land area is increased by 1% (one percent), the income of Arabica coffee farming will increase by 1.6989 percent. Labor wages have a negative and significant effect on Arabica coffee farming income, meaning that if labor wages increase by 1 percent, Arabica coffee farming income will decrease by -0.87908. Farming experience has a positive and significant effect on Arabica coffee farming income, meaning that if farming experience increases by 1% (one percent), then Arabica coffee farming income will increase by 0.1974 percent.Â Â Â